2015
DOI: 10.1016/j.neuropharm.2015.02.006
|View full text |Cite
|
Sign up to set email alerts
|

The human CHRNA7 and CHRFAM7A genes: A review of the genetics, regulation, and function

Abstract: The human α7 neuronal nicotinic acetylcholine receptor gene (CHRNA7) is ubiquitously expressed in both the central nervous system and in the periphery. CHRNA7 is genetically linked to multiple disorders with cognitive deficits, including schizophrenia, bipolar disorder, ADHD, epilepsy, Alzheimer’s disease, and Rett syndrome. The regulation of CHRNA7 is complex; more than a dozen mechanisms are known, one of which is a partial duplication of the parent gene. Exons 5-10 of CHRNA7 on chromosome 15 were duplicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
188
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(196 citation statements)
references
References 190 publications
(267 reference statements)
5
188
0
3
Order By: Relevance
“…Although the relevance of splice variants in a7 nAChR function still needs to be fully characterized, further efforts have been dedicated to more detailed analysis of the duplicate gene, which corresponds to exons 5-10 of CHRNA7 and is located 1.6 Mb centromeric to CHRNA7, which is now referred to as CHRFAM7A (for a recent detailed review, see Sinkus et al, 2015). The corresponding protein, dup a7, is widely expressed, but in lower levels than a7 nAChRs throughout the body but elevated in peripheral leukocytes (Villiger et al, 2002;Benfante et al, 2011.…”
Section: A the Chrna7 Gene And Its Variantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the relevance of splice variants in a7 nAChR function still needs to be fully characterized, further efforts have been dedicated to more detailed analysis of the duplicate gene, which corresponds to exons 5-10 of CHRNA7 and is located 1.6 Mb centromeric to CHRNA7, which is now referred to as CHRFAM7A (for a recent detailed review, see Sinkus et al, 2015). The corresponding protein, dup a7, is widely expressed, but in lower levels than a7 nAChRs throughout the body but elevated in peripheral leukocytes (Villiger et al, 2002;Benfante et al, 2011.…”
Section: A the Chrna7 Gene And Its Variantsmentioning
confidence: 99%
“…However, what is missing is the detection of the CHRFAM7A transcript, but as noted in a recent review the similarity of this gene with CHRNA7 renders difficult the query in genome-wide association studies. Nonetheless, CHRFAM7A was recently proposed to be associated with several cognitive deficits (Sinkus et al, 2015).…”
Section: A the Chrna7 Gene And Its Variantsmentioning
confidence: 99%
“…As recently reviewed by Costantini et al (2) and Sinkus et al (3), it was almost twenty years later that Gault et al (4) sequenced the human α7nAChR gene on chromosome 15q13-14 and found it to be structurally similar to that of all other species. At the same time, however, they noted the presence of a second, human-specific partially duplicated α7nAChR-like gene that localized 1.6 Mb 5′ upstream from human CHRNA7 (4).…”
Section: Introductionmentioning
confidence: 97%
“…Postsynaptically, a7 receptors mediate fast synaptic transmission, and in perisynaptic locations they modulate other inputs to neurons and activate a variety of signaling pathways through volume transmission (Gotti and Clementi, 2004;Jones and Wonnacott, 2004;Dani and Bertrand, 2007;Dickinson et al, 2008;Albuquerque et al, 2009;Sinkus et al, 2015) (Fig. 4).…”
Section: Introductionmentioning
confidence: 99%
“…Significant reduction of a7 in the brain, particularly in the hippocampus, has been reported in Alzheimer disease (Guan et al, 2000;Kadir et al, 2006) and schizophrenic patients (Schaaf, 2014;Dineley et al, 2015). The a7 gene, CHRNA7 on chromosome 15, is genetically linked to multiple disorders with cognitive deficits, including schizophrenia, intellectual disability, bipolar disorder, autism spectrum disorders, attention deficit hyperactivity disorder, epilepsy, Alzheimer disease, and sensory processing deficit (Sinkus et al, 2009(Sinkus et al, , 2015Schaaf, 2014;Dineley et al, 2015;Deutsch et al, 2016). A partial duplication of CHRNA7 resulting in the chimeric gene CHRFAM7A, which is present only in humans, has been associated with schizophrenia (Sinkus et al, 2009;Neri et al, 2012).…”
Section: Introductionmentioning
confidence: 99%